Cooking influence in tolerance acquisition in egg-induced acute food protein enterocolitis syndrome. - Miceli Sopo, S; Romano, A; Bersani, G; Fantacci, C; Badina, L; Longo, G; Monti, G; Viola, S; Tripodi, S; Barilaro, G; Iacono, I D; Caffarelli, C; et al. (Allergol Immunopathol (Madr), 2018)
BACKGROUND: Few studies on the age of resolution of Food Protein Induced Enterocolitis Syndrome (FPIES) induced by solid foods are available. In particular, for FPIES induced by egg, the mean age of tolerance acquisition reported in the literature ranges from 42 to 63 months. OBJECTIVE: We have assessed whether the age of tolerance acquisition in acute egg FPIES varies depending on whether the egg is cooked or raw. METHODS: We conducted a retrospective and multicentric study of children with diagnosis of acute egg FPIES seen in 10 Italian allergy units between July 2003 and October 2017. The collected data regarded sex, presence of other allergic diseases, age of onset of symptoms, kind and severity of symptoms, cooking technique of the ingested egg, outcome of the allergy test, age of tolerance acquisition. RESULTS: Sixty-one children with acute egg FPIES were enrolled, 34 (56%) males and 27 (44%) females. Tolerance to cooked egg has been demonstrated by 47/61 (77%) children at a mean age of 30.2 months. For 32 of them, tolerance to raw egg has been demonstrated at a mean age of 43.9 months. No episodes of severe adverse reaction after baked egg ingestion have been recorded. CONCLUSIONS: It is possible to perform an OFC with baked egg, to verify the possible acquisition of tolerance, at about 30 months of life in children with acute egg FPIES.